Depth analysis of border security space planning for the Malaysia-Thailand border in Rantau Panjang, Malaysia / Azizul Hairil Syukri Sabri and Mariam Felani Shaari - Sabri, Azizul Hairil Syukri; Shaari, Mariam Felani (UiTM Press, 2024)
This study conducts a depth analysis of the Rantau Panjang border checkpoint between Malaysia and Thailand, recommending the best possible design concept for its improvement. Examining the MalaysiaThailand border from historical, geopolitical, and economic perspectives, the study reveals the complexities of border management and highlights the need for more robust security measures. The study tackles the urgent issue of porous border checkpoints in Malaysia, particularly at Rantau Panjang, which calls for a critical assessment of the operational and spatial circumstances as they stand. The three objectives are to evaluate the current condition of the Rantau Panjang border facility, find best practices from local and international antecedents, and consider building a new type or upgrading the checkpoint, using a mixed-method study design that includes site visits, case studies, and questionnaires. The investigation reveals deplorable circumstances at Rantau Panjang, including unlawful activity and poor space design. The results recommend wider documentation counters, better direct circulation, and the incorporation of auxiliary programmes to reduce traffic and boost productivity. The importance of a comprehensive and flexible strategy for border security is emphasised in the study's conclusion, which also acknowledges the limitations brought on by financial and schedule constraints. Notwithstanding these drawbacks, the study makes a substantial contribution to the conversation on border security and national security, especially in light of West Malaysia's advantageous location.